Sex Differences in Nociceptin/Orphanin FQ Peptide Receptor-Mediated Pain and Anxiety Symptoms in a Preclinical Model of Post-traumatic Stress Disorder - Zhang, Yong; Schalo, Ian; Durand, Cindy; Standifer, Kelly M. (Frontiers in Psychiatry, 2019)
Nociceptin/Orphanin FQ (N/OFQ) is a neuropeptide that modulates pain transmission, learning/memory, stress, anxiety and fear responses via activation of the N/OFQ peptide (NOP or ORL1) receptor. Post-traumatic stress disorder (PTSD) is an anxiety disorder that may arise after exposure to a traumatic or fearful event, and often is co-morbid with chronic pain. Using an established animal model of PTSD, single-prolonged stress (SPS), we were the first to report that NOP receptor antagonist treatment reversed traumatic stress-induced allodynia, thermal hyperalgesia and anxiety-like behaviors in male Sprague-Dawley rats. NOP antagonist treatment also reversed SPS-induced serum and CSF N/OFQ increase and circulating corticosterone decrease. The objective of this study was to examine the role of the NOP receptor in male and female rats subjected to traumatic stress using Wistar wild type (WT) and NOP receptor knockout (KO) rats. The severity of co-morbid allodynia was assessed as change in paw withdrawal threshold (PWT) to von Frey and paw withdrawal latency (PWL) to radiant heat stimuli, respectively. PWT and PWL decreased in male and female rats within 7 days after SPS, and remained decreased through day 28. Baseline sensitivity did not differ between genotypes. However, while male NOP receptor KO rats were protected from SPS-induced allodynia and thermal hypersensitivity, female NOP receptor KO rats exhibited tactile allodynia and thermal hypersensitivity to the same extent as WT rats. Male NOP receptor KO rats had a lower anxiety index (AI) than WT, but SPS did not increase AI in WT males. In contrast, SPS significantly increased AI in WT and NOP receptor KO female rats. SPS increased circulating N/OFQ levels in male WT, but not in male NOP receptor KO, or WT or KO female rats. These results indicate that the absence of the NOP receptor protects males from traumatic-stress-induced allodynia and hyperalgesia, consistent with our previous findings utilizing a NOP receptor antagonist. However, female NOP receptor KO rats experience allodynia, hyperalgesia and anxiety-like symptoms to the same extent as WT females following SPS. This suggests that endogenous N/OFQ-NOP receptor signaling plays an important, but distinct, role in males and females following exposure to traumatic stress.